Redox Regulation of Autophagy in Cancer: Mechanism, Prevention and Therapy - Jingqiu He; Lixia Dong; Li Luo; Kui Wang (Life, 2022)
Reactive oxygen species (ROS), products of normal cellular metabolism, play an important role in signal transduction. Autophagy is an intracellular degradation process in response to various stress conditions, such as nutritional deprivation, organelle damage and accumulation of abnormal proteins. ROS and autophagy both exhibit double-edged sword roles in the occurrence and development of cancer. Studies have shown that oxidative stress, as the converging point of these stimuli, is involved in the mechanical regulation of autophagy process. The regulation of ROS on autophagy can be roughly divided into indirect and direct methods. The indirect regulation of autophagy by ROS includes post-transcriptional and transcriptional modulation. ROS-mediated post-transcriptional regulation of autophagy includes the post-translational modifications and protein interactions of AMPK, Beclin 1, PI3K and other molecules, while transcriptional regulation mainly focuses on p62/Keap1/Nrf2 pathway. Notably, ROS can directly oxidize key autophagy proteins, such as ATG4 and p62, leading to the inhibition of autophagy pathway. In this review, we will elaborate the molecular mechanisms of redox regulation of autophagy in cancer, and discuss ROS- and autophagy-based therapeutic strategies for cancer treatment.